Medical record review of deaths, unexpected intensive care unit admissions, and clinician referrals: detection of adverse events and insight into the system. Issue 2 (25th October 2005) - Dunn, K L; Reddy, P; Moulden, A; Bowes, G
Abstract : Aims and Methods: To determine whether a programme of continuous medical record review of deaths, unexpected intensive care unit (ICU) admissions, and admissions referred by medical and nursing staff for specific review, would provide a range of adverse events from which to gain insight into the healthcare system of a large paediatric referral hospital. A quality assurance programme was commenced in 1996. Results: Over a six year period there were 103 255 admissions; 1612 (1.6%) records were reviewed, from which 325 adverse events were detected. Events were associated with operations, procedures and anaesthesia (56.5%), diagnosis and therapy (24%), drug and fluid management (12.6%), and system issues (7%). Medical records were reviewed from 23 of the 28 clinical units. Review of the records and analysis of the adverse events triggered many system changes. Conclusions: The findings suggest that continuous medical record review may be a valuable method for the detection of adverse events and identifying system issues in children's hospitals.